Mus'ab 'Umayr: the great martyr of the muslim nation. - Jamaludin, Rosashrakiah; Mahmud, Murni (IIUM Press, 2011)
"Mus'ab 'bmay~, The Great Martqr of the Muslim Nation" as developed by using tu o-dimensional animation n hich focuses on Islamic History. This story as most detailed and fascinated about one of the companions of prophet Rasulullah (S.A.W) and his contribution and sacrifice tonards Islam. It is an edutainment that targeted audience between the ages of 7 to 15. Muslim or non-Muslim. children and teenagers, adults. parents and educators are encouraged to view it for educational purposes. The narrator uses English Language for the audio and the subtitle is in Malay Language. The storyline is based on ethical, moral and ha\ ing Islamic perspecti1.e in obtaining good issues in each story. The story is based on Islamic history and Al - Quran and the plots are dicided into three parts namely the beginning, climax, and ending